Nebulized glycyrrhizin/enoxolone drug modulates IL-17A in COVID-19 patients: a randomized clinical trial - Zendejas-Hernandez, Ulises; Alcántara-Martínez, Nemi; Vivar, Diana Tovar; Valenzuela, Fermín; Sosa Espinoza, Alejandro; Cervera Ceballos, Eduardo Emir (Frontiers in Immunology, 2024)
Introduction Glycyrrhizin (GA) and its derivative Enoxolone (18β), isolated from the Glycyrrhiza glabra plant, are two potential molecules for treating viral diseases. Both demonstrate to regulate immune system with antiviral and anti-inflammatory activities, with the latter mainly due to modulation of inflammatory cytokines. The aim of this clinical trial was to evaluate the safety and efficacy of a nebulized GA/18β drug for treating COVID-19 patients. Methods An open label, randomized, placebo-controlled clinical trial was conducted in Mexico City from January-August 2022 (Registration No. PROTAP-CLI-00). Clinical and biochemical parameters were recorded. Blood samples from patients were regularly collected to evaluate interleukins IL-4, IL-2, IL-1b, TNF-α, IL-17A, IL-6, IL-10,IFN-γ, IL-12, IL-8 and TGF-β1, as well as IgM and IgG against SARS-CoV-2. Two doses of the drug were used - 30/2 mg (dose A) and 90/4 mg (dose B). Results and discussion Both GA/18β doses modulated inflammatory response by reducing mainly IL-17A expression, which in turn kept IL-1β, IL-6, IL-8 and TNF-α interleukins unchanged, indicating significant modulation of key interleukin levels to prevent exacerbation of the immune response in COVID-19 patients. Early on, dose A increased IgM, while dose B induced expression of the antiviral IFN-γ. No severe side effects were seen with either dose, indicating nebulized GA/18β is a safe treatment that could be used for COVID-19 and potentially other viral infections involving inflammatory response.